Management of Practical Learning Facilities and Infrastructure in the Electrical Engineering Vocational Education Study Program Universitas Sultan Ageng Tirtayasa - Irwanto Irwanto; Bayu Saputra (9 772338317006)
Abstract: Management of Practical Learning Facilities and Infrastructure in the Vocational Education Study Program of Electrical Engineering, Sultan Ageng Tirtayasa University. The purpose of this study was to determine the planning, procurement, inventory, utilization of practical learning facilities and infrastructure in the electrical engineering vocational education study program, Sultan Ageng Tirtayasa University. The method in this study used a qualitative descriptive approach with data sources, namely the head of the PVTE department, the head of the laboratory and the assistant of the PVTE laboratory. Data collection techniques through observation, interviews, and documentation. Data analysis techniques in this study were data reduction, data presentation, and conclusion drawing. Checking the validity of the data in this study is the credibility test with observation persistence techniques and triangulation methods. The findings in this study state that the management of practical learning facilities and infrastructure carried out in the PVTE study program is quite good. This can be seen from: 1) planning of practical learning facilities and infrastructure through needs analysis, determining priority scales, budgeting, preparing proposals, (2) procuring practical learning facilities and infrastructure by first disbursing the budget according to the activity plan and the faculty budget. , then procure by purchasing equipment directly to the shop or factory using operational assistance funds. (3) inventory procedures for practical learning facilities and infrastructure are carried out by recording, coding, and reporting quarterly and annually, (4) practical learning facilities and infrastructure according to the schedule of practical courses and to achieve effective and efficient practical learning. The operation of the equipment uses a manual in the form of a manual and follows instructions from the lecturer or aslabKeywords: Management, Facilities and Infrastructure, Planning, Procurement, Inventerization DOI : 10.23960/jmmp .v8.i3.2020